COLLECTIVE HABITUATION TO ATTACH BELIEFS OF INDIGENOUS COMMUNITIES IN VILLAGE-OWNED ENTERPRISE (BUMDes) ROUTINES - Ahmad Imron Rozuli (Jurnal Sosiologi Agama, 2022)
This article serves to present a different perspective about Village-Owned Enterprise (BUMDes), that sustainable BUMDes needs touches of structural and religious values that adhere to communities. The strength of BUMDes is not on the regulation from the village authority. Further, the core values of religious beliefs and community structure renovate the implanted BUMDes knowledge to a referral guideline to behave amidst the communities. A qualitative research approach was applied in the form of a descriptive case study, located in Kutuh Village, Badung Regency, North Bali. The research indicated that the powerfulness of Tri Hita Karana signified beliefs and ancestral values as cultural and symbolic capitals concerning environment, community, and divinity. In this context, three sorts of lands as resources were developed by agents, especially traditional leaders and their apparatus. They were able to restructure customary laws concerning activities. Furthermore, the agents and structure were also able to regulate the conducts of the indigenous people as the roots of mind-shaping for the local people. This was the reason why beliefs could attach to the structure of thought of the indigenous people so that any activities in BUMDa (Bagha Utsaha Manunggal Desa Adat/Traditional Village Integrated Business Entity) can be collectively habituated as routines.